Impact of ChatGPT technology on economic development - V. А. Grudinina; I. V. Merkulova (Вестник Северо-Кавказского федерального университета)
Introduction. Widespread digitalization leads to the creation of new technologies. At the present stage, artificial intelligence has been introduced into all spheres of public life: education, medicine, mechanical engineering and agriculture. AIpowered product companies are promising to automate all sorts of tasks that have been previously considered exclusively the realm of human creativity and reasoning, from writing texts to creating graphs, summarizing and analyzing data. Despite all the astonishing advances in artificial intelligence and other digital tools over the past decade, their success in improving the well-being of the population remains in question. Goal. Assessment of the impact of the development of the new GPT-3.5 language model on the economy. Materials and methods. The study is based on the analysis of the works of national and foreign economists in the field of artificial intelligence. During the study, three types of methods were used: theoretical, practical and special. The methodological basis is the theoretical methods of research. Results and discussion. In the course of the work, an analysis was made of the functioning of ChatGPT at the present time. An assessment of the current state of the market for products based on artificial intelligence technology was carried out. The advantages and disadvantages of the new GPT-4 language model are analyzed. Conclusion. Based on the results of the study, we can conclude that ChatGPT can become a powerful driver for the development of the digital economy. The new language model is not without drawbacks in the form of an outdated information base. Despite this, a new generation of chatbots is gaining the ability to recognize speech and graphic images.